Park Jin Young’s Politeness Strategies in The America-to Korea (A2K) Survival Show - Sindangsari, Laura Putri; fitriyah, Aidatul; Aydinovich, Gashimov Elchin (Lingua : Journal of Linguistics and Language, 2024)
This study investigated the politeness strategies used by Park Jin Young when commenting on the American contestants’ performance in the A2K show and its factors. The aim was to find what types of politeness strategies Park Jin Young used and the factors that influenced him to choose those in the A2K show. The method used is a qualitative method using Scollon et al.'s (2012) politeness theory. The result showed that Park Jin Young used more involvement than an independence strategy. The factors influencing it are the power and distance factors, revealing his implementation of a hierarchical politeness structure. In addition, the weight of imposition factor reveals that even though Park Jin Young tries to adapt to American politeness when commenting on American contestants' performances, he still maintains his identity as a Korean by using independent strategies